Pelatihan Dosen Keperawatan dalam Penggunaan Aplikasi RPS Digital - Risqi Wahyu Susanti; Rosani Naim; Grace Tedy Tulak; Ekawati Saputri; Muhdar Muhdar; Rosmiati Rosmiati; Abd. Gani Baeda (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Improving the quality of learning can be done when there is a planned process that is effective, effective, and relevant. Technological innovation is indispensable in making Semester Learning Plans (RPS) with a digital system, where this digital RPS will be able to improve the quality of the learning process planning by homogenizing the format and systematics of the RPS and can make the RPS more effective and efficient, especially for Nursing lecturers. The method used in this service is guided training so that the result of this training is that nursing lecturers can use the digital RPS application and can generate RPS through the use of the digital RPS application. All training participants felt that this application made it easy to make RPS so that the lecturers chose this application in making RPS every semester.